Çiftlik Formation through Title Deeds in the Ottoman Black Sea (1800-1850s) - Sahin, Canay (BRILL, 2025)
This article aims to contribute to the discussion on the meaning, timing and formation of ciftliks by analysing the Survey of Estates in Canik (Canik & Ccedil;iftlikat Defteri) undertaken during 1853-1854, which could be considered as the register of ciftlikized state owned lands. The paper then moves to point out the relationship between the empowerment of the Hazinedarzade dynasty and the expansion of their estates through the legal mechanisms of temlik (sultanic grant), vak & imath;f (charitable foundation) and local court certificates during the pre-Tanzimat period. The third section concentrates on the local and central administrative-legal procedures involved in determining ownership rights over ciftliks, by paying attention to the alliance between local judiciaries and ciftlik owners. The fourth and final section presents the distribution of ciftlik owners and the actors who sealed the title deeds belonging to estate owners, as well as the uncertainties surrounding the title deeds.
Keywords: ciftlik formation; title deed ( tapu); Hazinedarzades; Canik; Black Sea; History